GAS CHROMATOGRAPHY MASS SPECTROSCOPY ANALYSIS AND PREDICTION OF BIOACTIVITIES IN THE CHLOROFORM EXTRACT OF HALYMENIA DILATATA ZANARDINI (RED ALGAE) COLLECTED FROM MANDAPAM, TAMIL NADU, INDIA - RAJA E, FREDRICK; PAUL J, JOHN PETER (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: This study was to determine the presence of biochemicals and prediction of bioactivities in the chloroform extract of Halymenia dilatata Zanardini (Red algae) collected from Mandapam, Tamil Nadu, India. Methods: The active biological components in the chloroform extract of H. dilatata Zanardini were studied using gas chromatography mass spectroscopy (GC-MS), and the biological activities were predicted by prediction activity spectra for substances technique. Results: The analysis revealed the two bioactive components such as N-Hexadecanoic acid (5.384%) and 1,2-Benzenedicarboxylic acid, Mono(2- Ethylhexyl) Ester (94.616%). In 1,2-Benzenedicarboxylic acid, Mono(2-Ethylhexyl) Ester, 1933 biological activities were predicted. Among the biological activities, 74 were highly active and their Pa score is above 70%. In Pa>0.7, there a 15 different activities are predicated including antitumor (91.5%) followed by anti-inflammatory (89.7%), antimicrobial (84.7%), anti-inflammatory (74.5%), etc. Conclusion: The present study provided the bioactive components present in the chloroform extract of H. dilatata Zanardini by GC-MS analysis and the prediction of biological studies by prediction of activity spectra for substances.